2015
DOI: 10.1002/art.39170
|View full text |Cite
|
Sign up to set email alerts
|

Associations With Smoking and Shared Epitope Differ Between IgA‐ and IgG‐Class Antibodies to Cyclic Citrullinated Peptides in Early Rheumatoid Arthritis

Abstract: Objective Smoking and HLA–DRB1/shared epitope (SE) alleles are risk factors for rheumatoid arthritis (RA) characterized by seropositivity for antibodies targeting citrullinated proteins (ACPAs)/cyclic citrullinated peptides (anti‐CCP). Previously, mainly IgG‐class antibodies have been studied. IgA‐class antibodies are to a great extent related to mucosal immunity. The aim of this study was to explore interrelations between cigarette smoking, presence of SE, and seropositivity for circulating IgA and/or IgG ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 33 publications
1
45
0
1
Order By: Relevance
“…This contention is supported by findings of structural abnormalities of lung parenchyma in patients with untreated, early ACPA-positive RA [41]. These were 5 associated with high concentrations of ACPA in bronchoalveolar lavage fluid relative to those of blood [35,39].…”
Section: Smoking and Ramentioning
confidence: 81%
See 1 more Smart Citation
“…This contention is supported by findings of structural abnormalities of lung parenchyma in patients with untreated, early ACPA-positive RA [41]. These were 5 associated with high concentrations of ACPA in bronchoalveolar lavage fluid relative to those of blood [35,39].…”
Section: Smoking and Ramentioning
confidence: 81%
“…The smoking/SE allele interaction is, however, complex [40]. This is clearly illustrated by the findings of a recent study which reported that ever-smoking per se is associated with production of ACPA of the IgA isotype, possibly consistent with a pulmonary origin, while SE in the absence of smoking is associated with ACPA of the IgG isotype, and the combination of smoking and SE with seropositivity for both isotypes [41].…”
Section: Smoking and Ramentioning
confidence: 96%
“…In the present study, we used part of the TIRA2 cohort (n = 504), which enrolled patients with recent-onset RA between 2006 and 2009 (37). Symptom duration was at least 6 weeks but less than 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…These results were confirmed by Manfredsdittor et al [129] in a prospective study that showed that IgA RF was associated with a poor prognosis. Svärd et al reported that in anti-CCPpositive patients with RA, a history of Bever smokingŵ as associated only with IgA antibodies [130], and the same group reported in 2016 that circulating secretory IgA antibodies against cyclic citrullinated peptides in early rheumatoid arthritis associate with inflammatory activity and smoking [131]. Mikuls et al [132] examined cigarette smoking and RA-related features in African Americans.…”
Section: Iga Autoantibodies and Smokingmentioning
confidence: 99%